On the impact of syllabic constituency on nonword repetition: preliminary data from typical development for the validation of LITMUS-QU-NWR-EP - Catarino, Inês (2021)
Nonword repetition is a relevant task in clinical phonological assessment. However, few authors have considered the impact of syllable constituency on child performance in such task. In this study, we analyse the contribution of syllable constituency in nonword repetition through the validation of a new test (LITMUS-QU-NWR-EP) adapted to European Portuguese (EP). Two syllable structures were considered: lateral coda (both in word-medial and word-final position) and branching onsets (obstruent + lateral clusters). Results from typically developing children, aged 5 to 8 years, showed generalized difficulties in both structures, although codas were less problematic than branching onsets. Portuguese child performance contrasts with the data obtained for the French version of the instrument (LITMUS-QU-NWR-FR), given the overall lower performance found for EP, and the preference for codas over branching onsets, unlike attested for French children. A comparative analysis shows that nonword repetition difficulties in what concerns syllabic constituency may be language dependent. Clinical implications for EP are discussed.